IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 16 TAHUN 2011 TENTANG KOMUNITAS INTELIJEN DAERAH DI PROVINSI KALIMANTAN TIMUR - Edy Haryata (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The Role of the Community of Regional Intelligence (Kominda) every single day needed for goverment administration, so that minister of home affairs publish the ministerial regulation No. 16 Tahun 2011 about Community of Regional Intelligence (Kominda). East Kalimantan also publish Guvernour Rule Number 82 in 2011 about Community of Regional Intelligence. Generally, the Kominda’s assigment is helping Local Goverment of East Kalimantan and Coordinating political information, economic, social, cultural, defense, peace, and public order. The Challange of the rule No. 16 in 2011 such as there is not socializing to the people then low knowledge about “Intelligence” for half of Kominda members and there is not assigment divide clearly.